The Impact Of Credit Risk On The Financial Performance Of Banks In Indonesia Listed On The Indonesian Stock Exchange For The Period 2018 - 2022 - Dendy Mohammad Prabowo; Richy Wijaya (CV. AFDIFAL MAJU BERKAH, 2024)
Banking activities collect funds from customers and distribute credit to customers in the form of loans that are added with interest for the bank's opinion. Lending activities provided by banks have risks that must be mitigated to avoid large losses and adversely affect the bank's financial performance. This study used panel data regression method with sample of 35 Indonesian Banks listed on the Indonesia Stock Exchange with the period 2018 - 2022. Referring to the main research, bank financial performance is measured by return on assets and net interest margin, while bank risk is measured by the variables non-performing loans, capital adequacy ratio, loan loss provision ratio, and cost per loan ratio, this study also added new control variables, such as bank size and leverage. The results of this study found that there is an impact between NPL with ROA, LLPR with ROA, CAR with NIM, and CPLR with NIM. While there is no impact of CAR with ROA, CPLR with ROA, NPL with NIM, and LLPR with NIM.